Travel during COVID-19 pandemic in Libya: reasons of travel, disease importation and travel regulations. Issue 1 (1st January 2021) - Ramadan, Ahmad M.; Ibrahim, Khaled M; Belaid, Saadeddin Mohammed; Abusanina, Mohamed Salem; Ben Elfghi, Mohammed; Abughnia, Elmundr; Elkikkli, Ahmed; Alhudiri, Inas M; Elzagheid, Adam
ABSTRACT: Restriction of mobility between countries is an important regulatory measure to combat pandemics such as the coronavirus disease 2019 (COVID-19). Currently, PCR testing is required to enter the Libyan borders. However, no post-travel quarantine is employed. In this report, we briefly discuss travel regulations in Libya during the COVID-19 pandemic and disease importation by travelers. The results showed that almost half of the sample travel because of health care and therapy reasons. Tunisia was the most visited destination mainly for trading and business and receiving healthcare. Importantly, 13% of asymptomatic travelers were SARS-CoV-2 positive. Issues regarding repeated testing among very frequent travelers and variant importation needs to be addressed in a more efficient manner.